Extended Rationality, Altruism and the Justification of Moral Rules - Stefano Zamagni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
Ever since A. Smith reasoned about men's Moral Sentiments, as well as the nature and causes of the Wealth of Nations, the relation between ethics and economics has been an issue of scholarly interest.
Keywords: 330